PEDAGOGI BERASASKAN PENDEKATAN INDUKTIF DAN DEDUKTIF: PRAKTIS DALAM PENDIDIKAN KEWANGAN ISLAM: PEDAGOGY BASED ON INDUCTIVE AND DEDUCTIVE APROACHES: PRACTICE IN ISLAMIC FINANCE EDUCATION - Tengku Kasim, Tengku Sarina Aini; Mansor, Fadillah (Online Journal of Islamic Management and Finance (OJIMF), 2021)
The aim of this article is to study the inductive and deductive approaches, and to analyze their practices in teachers teaching in the context of Islamic finance areas. These approaches are explained in detail based on theoretical aspects and how they can be implemented in teaching and learning process among the teachers in higher education by giving some examples of Islamic finance as a case study. This study shows the relationship between the identification of these approaches in teaching and learning with the usage of the approaches efficiently, thus it will influence to the maximum course learning outcomes. Hence, identification of the approaches in teaching and learning is vital due to the role of teachers is not only seen as transferring knowledge and skills to the students but also ensuring the students show understanding and practice the teaching inputs. Therefore, the identification of the right approach will ease the process of usage the approach effectively towards achieving the learning outcomes as required. In conclusion, the identification and the practice of teaching approach accurately will make sure the teaching and learning process are conducted relevantly and appropriately to the stated educational objectives and the course learning outcomes.